Colloidal synthesis of lead-free all-inorganic Cs3Sb2BrxI9-x nanocrystals. Issue 4 (2nd October 2019) - Gan, Weijiang; Lou, Sunqi; Wang, Jing
Abstract : Environment-friendly lead-free perovskite nanocrystals (NCs) are highly desirable in terms of optoelectronic applications. Reported herein is the synthesis of perovskite-related Cs3 Sb2 Br9 NCs through a simple hot-injection approach. The morphologies and optical properties of NCs were controlled and optimized by varying the reaction temperature, time, and volume of surface ligands. Meanwhile, the Cs3 Sb2 Br9 NCs showed bandgap emission in the blue region centered at 470 nm, and 63 nm full width at half maximum (FWHM). In addition, the Cs3 Sb2 Br9 NCs displayed high stability when immersed in a polar solvent like ethanol. It was also found that the bandgaps of the Cs3 Sb2 Brx I9-x NCs could be adjusted by regulating the composition of halogen.